The Effect of Nitrogen Partial Pressure and Substrate Temperature on the Characteristics of Photocatalytic N:TiO2 Thin Films deposited by Filtered Vacuum Arc Deposition - Goldenberg, Eda; Burstein, L.; Chayun-Zucker, Ines; Avni, Rudi; Boxman, Raymond L. (International Conference on Plasma Surface Engineering, 2013)
Nitrogen doped Titanium Oxide (N:TiO2) thin films were deposited using filtered vacuum arc deposition, and their structure, composition and morphology were studied as functions of the total pressure, N2/O2 gas ratio and the substrate temperature. The film structure, surface morphology, and composition were determined by XRD, AFM and XPS. The optical characterization of the films was determined with spectrophotomery and ex-situ variable angle spectroscopic ellipsometry (VASE). In addition to the effects of other deposition conditions such as arc current, total deposition pressure, and post-deposition annealing on the film characteristics, photocatalytic activity was also determined as a function of deposition parameters and results were discussed.